Patient Decision Aid (PDA) for Patients with Rheumatoid Arthritis Reduces Decisional Conflict and Improves Readiness for Treatment Decision Making - Pablos, José Luis (Patient, 2019)
OBJECTIVES: The aim of this study was to develop and assess the effectiveness of a patient decision aid (PDA) to support treatment decision making in Spanish patients with moderate-to-severe rheumatoid arthritis (RA) who fail to achieve the therapeutic goal with the current disease-modifying antirheumatic treatment strategy. METHODS: The PDA was developed in accordance with the International Patient Decision Aids Standards recommendations. A steering group led the project. Three literature reviews and two focus groups were performed to develop the PDA prototype. To check its comprehensibility, acceptability, and feasibility, alpha-testing was performed using the Decision Support Acceptability Scale (DSAS). Beta-testing was conducted to assess preliminary evidence of PDA efficacy using the Decisional Conflict Scale (DCS) before and after PDA use. Readiness was evaluated using the Preparation for Decision Making Scale (PDMS). RESULTS: The PDA included (1) a brief description of RA, (2) treatment information, and (3) a values clarification section. Alpha-testing revealed that most patients considered that the information was presented in a good or excellent way and it could help clarify their values and facilitate treatment decision making. Most rheumatologists agreed that the PDA was easy to understand, to use, and allowed them to reach a shared decision. Beta-testing showed that PDA significantly reduced overall patients’ decisional conflict [33.2 (DE: 21.4) vs 24.6 (23.5); p < 0.001] and prepared the patient for decision making [PDMS: 67.5 (21.0)]. CONCLUSIONS: We developed a PDA for Spanish patients with moderate-to-severe RA that reduces patients’ decisional conflict and increases their readiness for decision making. The use of this PDA in routine clinical practice may improve the quality of the decision-making process and the quality of the choices made. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40271-019-00381-y) contains supplementary material, which is available to authorized users.